Top Ten Questions Male Sexual Abuse Survivors Want to Know from Health Care Research. Issue 8 (14th September 2018) - Cook, Joan M.; Anderson, Christopher; Simiola, Vanessa; Ellis, Amy E.
ABSTRACT: Sexual abuse is an often overlooked public health issue for boys and men. Given its prevalence and well-documented connection to mental and physical health disorders, the relevance of male survivor input and engagement in health care research is profound. Using a community-based participatory research design, an in-person focus group with male survivors of sexual abuse and researchers was conducted. This paper describes the top ten research questions male sexual abuse survivors would like to have answered. Survivors were most interested in knowing how sexual abuse and assault impact men's emotional and sexual functioning, what factors are involved in preventing and treating sexual assault-related emotional distress, and what can be done to prevent sexual abuse of boys and men. The fact that some of the questions survivors expressed an interest in knowing about have actually previously been investigated by researchers suggests a disconnect in translating evidence-based findings. Clinical and research implications include designing outreach interventions and gender-specific psychoeducation to increase engagement and access to care for men.